REVIEW. THE PENDING UTOPIAS. A BRIEF HISTORY OF THE WORLD SINCE 1945 - Velasco Martínez, Luis (Journal of the Spanish Institute for Strategic Studies, 2018)
Author: NÚÑEZ SEIXAS, Xosé Manoel. Barcelona. Editorial Crítica 2015.ISBN:-978-84-9892-837-2. (384 pages)